Basic Concepts Of Considerations And Decision-Making Strategies In Educational Leadership - Muchtarom, Muchtarom (The International Journal of Education Management and Sociology, 2023)
This research aims to find out the basic concepts of consideration and what strategies should be used by an educational leader in making decisions. The method used is a qualitative research method. This research is a literature study. The results of this study are as follows: (1) The principal in the decision-making process must pay attention to the implementation technique by first identifying the problem. Principals as policy makers need to understand the decision-making steps. (2) What becomes the basis for consideration in a leader's decision-making are intuition, facts, authority, and rationale. (3) A leader will be seen from his form of existence in making decisions and determining his policies. An effective leader is a leader who is able to make decisions and make relevant policies. (4) A leader must think about the consequences of an action before making a decision. (5) The strategies that need to be carried out in the decision-making process are: (a) Identifying a problem. (b) Clarify and prioritize goals. (c) Creating choices. (d) Choose the most appropriate option